2011
DOI: 10.1111/j.1440-1681.2011.05562.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple factors are required for the prediction of metabolic syndrome

Abstract: We read with great interest the paper by Xia et al., 1 who reported an association between the metabolic syndrome (MetS) and liver enzymes by the following two methods. After setting optimal cut-off values for liver enzymes in MetS by receiver-operating characteristic (ROC) curve analysis, logistic regression analysis was conducted to predict MetS by each liver enzyme. They concluded that MetS was significantly associated with increased serum levels of alanine aminotransferase (ALT) and c-glutamyl transpeptida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
1

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…Even after adjustment for other liver enzyme levels, ALT and GGT were still significantly associated with MS in our study, whereas Kawada 1 showed that GGT was the only liver enzyme significantly associated with MS. One possible explanation for the difference may be the study population. The study of Kawada was a prospective community‐based cohort focusing on the risk factors for the new onset of MS, with 2 years of follow up, and individuals with diabetes, hypertension, dyslipidaemia, hyperuricaemia and coronary and/or cerebrovascular disease were excluded from the study 1 . However, in our study we enrolled all participants with and without current MS, even though it was a cross‐sectional study 2 .…”
contrasting
confidence: 76%
See 1 more Smart Citation
“…Even after adjustment for other liver enzyme levels, ALT and GGT were still significantly associated with MS in our study, whereas Kawada 1 showed that GGT was the only liver enzyme significantly associated with MS. One possible explanation for the difference may be the study population. The study of Kawada was a prospective community‐based cohort focusing on the risk factors for the new onset of MS, with 2 years of follow up, and individuals with diabetes, hypertension, dyslipidaemia, hyperuricaemia and coronary and/or cerebrovascular disease were excluded from the study 1 . However, in our study we enrolled all participants with and without current MS, even though it was a cross‐sectional study 2 .…”
contrasting
confidence: 76%
“…
We appreciate the thoughtful comments by Kawada. 1 The purpose of our study 2 was to detect the association between liver enzymes and metabolic syndrome (MS) and, further, to determine the optimal cutoff values for liver enzymes in MS in 1503 individuals from a physical examination centre. We concluded that both aminotransferase (ALT) and c-glutamyl transpeptidase (GGT) were significantly associated with MS in our study.
…”
mentioning
confidence: 99%